Green Corrosion Inhibitors for Metal and Alloys Protection in Contact with Aqueous Saline - Paez-Collio, M; Paez-Collio, M; Jimenez-Arevalo, V; Jimenez-Arevalo, V (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Corrosion is an inevitable and persistent issue that affects various metallic infrastructures, leading to significant economic losses and safety concerns, particularly in areas near or in contact with saline solutions such as seawater. Green corrosion inhibitors are compounds derived from natural sources that are biodegradable in various environments, offering a promising alternative to their conventional counterparts. Despite their potential, green corrosion inhibitors still face several limitations and challenges when exposed to NaCl environments. This comprehensive review delves into these limitations and associated challenges, shedding light on the progress made in addressing these issues and potential future developments as tools in corrosion management. Explicitly the following aspects are covered: (1) attributes of corrosion inhibitors, (2) general corrosion mechanism, (3) mechanism of corrosion inhibition in NaCl, (4) typical electrochemical and surface characterization techniques, (5) theoretical simulations by Density Functional Theory, and (6) corrosion testing standards and general guidelines for corrosion inhibitor selection. This review is expected to advance the knowledge of green corrosion inhibitors and promote further research and applications. © 2024 by the authors.